ANALISIS KRITIS HADITS TENTANG SIFAT MUKMIN DENGAN PENDEKATAN SIMULTAN DAN PERSPEKTIF MULTIKULTURAL - Moch. Bachrurrosyady Amrulloh (Universitas Islam Lamongan, 2019)
This article is aimed at finding out and understanding the quality and the meaning of hadith with a simultaneous approach. This research raises the questions on what the hadith research method with a simultaneous approach is? and what the quality of the hadith about